1989
DOI: 10.1016/s0022-5347(17)38895-x
|View full text |Cite
|
Sign up to set email alerts
|

The Prune Belly Syndrome: A Comprehensive Approach to Management

Abstract: Our approach to management of the prune belly syndrome entails a program of comprehensive early reconstruction, including abdominoplasty, bilateral orchiopexy, reduction cystoplasty, and selective ureteral tailoring and reimplantation. Of 20 patients with the prune belly syndrome treated at our institution during the last 18 years 15 underwent comprehensive reconstruction. Abdominoplasty was performed in 16 patients. Results were evaluated as to cosmetic appearance, functional performance, and preoperative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Fallat et al reported on 15 patients who had undergone early urinary reconstruction, consisting of ureteric tapering, reimplantation and reduction cystoplasty. In all patients, there were no changes in pre-and postoperative serum creatinine levels (Level 3) [39]. Bukowski et al examined the reduction cystoplasty element of their urinary reconstructions.…”
Section: Urinary Tractmentioning
confidence: 98%
See 4 more Smart Citations
“…Fallat et al reported on 15 patients who had undergone early urinary reconstruction, consisting of ureteric tapering, reimplantation and reduction cystoplasty. In all patients, there were no changes in pre-and postoperative serum creatinine levels (Level 3) [39]. Bukowski et al examined the reduction cystoplasty element of their urinary reconstructions.…”
Section: Urinary Tractmentioning
confidence: 98%
“…This is likely due to the poor peristalsis and inherent muscular deficiencies present in the PBS ureter and bladder. Vesico-ureteric junction (VUJ) obstruction requiring re-operation in 40% of patients and failure of resolution of VUR post-reimplant in 30% of patients was reported in one series [39].…”
Section: Urinary Tractmentioning
confidence: 99%
See 3 more Smart Citations